Intimate partner violence and victims - Gopalan, Rejani Thudalikunnil (Victimology, 2022)
Intimate partner violence or domestic violence is a growing crime across the world, and it affects the victim physically, emotionally, psychologically, socially, and economically; in short, it may shatter the victims. The forms of the abuse can be different, and mostly women are the primary victims. It is also noticed that domestic violence is intergenerational, and prevalence is more where gender inequality exists highly. There is a high risk for victims to develop posttraumatic stress disorder and other mental health issues. This chapter would throw light on definition, types, prevalence, theories of intimate partner violence, risk factors, impacts, theories, forensic investigations, preventions, and interventions. It is important to explore the vulnerable and risk factors for IPV at multilevels as well as the factors favouring the attitude of IPV on individual, relationship, social, and cultural levels. The traditional way of looking into the problems of IPV like male–female issues needs to be changed to different dimensions so as the dynamics. The legal aid and policies for IPV mainly targeted to help females in many countries, and this stance has to be changed when looked into the fact of increased number of victimizations to males while female as perpetrator. As IPV is more closed to sociocultural factors, policies in the criminal justice system to be amended in the view of scientific findings in the field and training programmes are required for those professionals involved in forensic investigations and procedures related to IPV.